Desenvolvimento profissional docente: desafios e tensionamentos na educação superior na perspectiva dos coordenadores de área e de curso - Felden, Eliane de Lourdes (Universidade do Vale do Rio dos Sinos, 2013)
The present research aims to investigate the professional development of teachers by listening to area coordinators and course coordinators of Higher Education regarding the challenges and tensions of teacher training. The study approaches the theme involving three foundation axis: Higher Education in Brazil, the teaching of higher education, continuum training and professional development of university teachers examined with the support of Anastasiou; Alves (2010), Balzan (1985, 2000), Behrens (2005), Charlot (2005, 2000); Cunha (1989, 1995, 1996, 2003, 2005, 2006a, 2006b, 2007, 2009, 2010, 2012), Formosinho (1991, 2009), Frigotto (2011), Imbernón (2009, 2010, 2011), Leite (2003, 2005, 2010, 2012), Masetto (1998, 2000), Nóvoa (1989, 1994, 1995, 1999, 2002, 2007, 2008), Rios (2006, 2008, 2012), Veiga (2006, 2008, 2011, 2012), amongst others. The research uses as base for analysis data collection, space for the comprehension of professional development of teachers in the departments of Human Science; Linguistics and Arts; Health Science; Applied Social Science; Biological Science; Exact and Earth Science; Engineering and Computer Science at the Universidade Regional Integrada do Alto Uruguai e das Missões – URI, Santo Ângelo Campus – RS. The work is a qualitative work in which semi-structured interviews were used with the coordinators of the areas as well as course coordinators, who are also teachers, with the aim to identify and understand the challenges and tensions of qualifying the teaching actions at university. Among the challenges and tensions are: arranging the many teaching activities with scientific production; responding to the demands of society in order for the higher education institute to have the solution of present issues; responding to the indices and assessment tools proposed by the Education and Culture Ministry; the degrees crisis, amongst others. These professionals acknowledge that the formation processes in the institution are scarce and need to be intensified, as there is a demand for permanent training and because the science fields are in continuous development. It was possible to infer that to qualify the teaching action at university means to invest on the continuous training of the professionals as an essential condition for their development, in the attempt of overcoming the challenges and tensions which they went through. It is understood that the articulate work of the university and its teachers may cause some important paradigmatic ruptures in the teaching and learning process, thus implying institutional investments in Teacher Development. Professionals believe that enhancing teacher training requires the establishment of spaces for study and reflection, assuring the role of teachers.
Keywords: Training; Teachers development; University teaching; Higher education; Formação; Desenvolvimento profissional docente; Docência universitária; Educação superior; ACCNPQ::Ciências Humanas::Educação